2021
DOI: 10.1111/1462-2920.15520
|View full text |Cite
|
Sign up to set email alerts
|

How do soil microbes exert impact on soil respiration and its temperature sensitivity?

Abstract: Understanding how soil microorganisms influence the direction and magnitude of soil carbon feedback to global warming is vital to predict future climate change. Although microbial activities are major contributors to soil respiration (R S ) and its temperature sensitivity (Q 10 ), the mechanisms underpinning microbial influence on R S and Q 10 remain unclear. Coupling variation partitioning analysis (VPA), correlation analysis and multiple stepwise linear regression analysis, we illustrate that bacteria mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…When the T S is low, the activities of some critical enzymes that control R S decrease, resulting in a lower R S rate. On the monthly scale, with increasing T S , the R S rate starts to increase in April, reaches a maximum value in July, and then gradually decreases to a lower value in October, which is consistent with the results of Tong et al (2021) . Our results differ from the results of Wen et al (2018) .…”
Section: Discussionsupporting
confidence: 90%
“…When the T S is low, the activities of some critical enzymes that control R S decrease, resulting in a lower R S rate. On the monthly scale, with increasing T S , the R S rate starts to increase in April, reaches a maximum value in July, and then gradually decreases to a lower value in October, which is consistent with the results of Tong et al (2021) . Our results differ from the results of Wen et al (2018) .…”
Section: Discussionsupporting
confidence: 90%
“…Negative (Wang et al, 2018) or no (Ding et al, 2016) association of Q 10 with F:B ratio have been reported. The negative relationship between RII Q 10 and RII F:B reflects the adaptation strategies of fungi and bacteria to temperature (Dell et al, 2014; Tong et al, 2021; Wang et al, 2021). Fungi generally have a greater negative heat capacity than bacteria and thus exhibit a higher Q 10 (Alster et al, 2016; Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The modularity values of the bacterial and fungal cooccurrence network that were greater than 0.4 for all DRW treatments, except for the 4-cycle DRW treatment for bacteria, indicated the modular structures of both bacterial and fungal networks (Jiao et al, 2021). The species within the same modulars were reported to have similar ecological niches (Tong et al, 2021). In addition, the bacterial cooccurrence network was more complex (i.e., more nodes and edges and larger average degree) and had more diverse niches (higher modularity) in the 4-cycle DRW treatment, whereas the co-occurrence network for fungi showed the opposite trend, which did not support our second hypothesis.…”
Section: Contrasting Responses Of Bacterial and Fungal Communities To...mentioning
confidence: 93%